Ion-selective membrane-integrated water-gated AlGaN/GaN HEMT for high-stability detection of agricultural herbicides - Firdaus, Amirul; Fauzi, Najihah; Ismail, Shuhadah; Hamzah, Nur Atiqah; Shukor, Rashidah; Kawarada, Hiroshi; Falina, Shaili; Syamsul, Mohd (Elsevier B.V., 2025)
This research work presents the development and characterization of a water-gated high electron mobility transistor (WGHEMT) sensor for real-time detection of herbicides, specifically glyphosate, paraquat, and diquat. Conventional FET-based sensors often suffer from design rigidity, as they are not modular and typically require complex fabrication steps for each specific target analyte. These limitations hinder their reusability for practical environmental monitoring applications. The WGHEMT utilizes a dual-pool electrolyte-gating mechanism with a replaceable ion-selective membrane (ISM) to modulate charge interactions at the AlGaN/GaN interface. Electrical and potentiometric responses were evaluated for both stock and commercial formulations, revealing that WGHEMT performance is highly dependent on herbicide concentrations. Paraquat consistently demonstrated the highest sensitivity due to its dicationic structure, while commercial glyphosate showed enhanced performance, attributed to improved ionic mobility from surfactants. Current sensitivity reached up to 761.029 µA/mg L−1 for commercial paraquat with excellent linearity (R2 = 0.96173). The WGHEMT exhibited strong stability and repeatability, with drift values under 1 % during time-dependent measurements for all herbicides concentrations. The WGHEMT adopts a modular approach through its interchangeable ISM, allowing flexible detection of various herbicides without requiring structural modifications. These results highlight the WGHEMT sensor's high sensitivity, reliability, and suitability for field-based herbicide monitoring, underscoring the importance of calibrating WGHEMTs with commercial formulations for accurate environmental assessment.